Kewartawanan dan media era digital : isu-isu semasa - Chamil Wariya, Datuk, 1952- (Kuala Lumpur : Malaysian Press Institute, 2012)
On online journalism in the contemporary age of digital media in Malaysia; collected articles.
Includes bibliographical references (pages 237-240) and index.
In Malay.
Keywords: Online journalism -- Malaysia; Mass media and technology; Journalistic ethics -- Malaysia